2017
DOI: 10.1039/c7py00441a
|View full text |Cite
|
Sign up to set email alerts
|

Increasing bacterial affinity and cytocompatibility with four-arm star glycopolymers and antimicrobial α-polylysine

Abstract: A series of four-arm star copolymers, incorporating glycopolymer and antimicrobial polypeptide domains, was developed in the design of forthcoming anti-infective agents. Mannose, glucose, and galactosebased glycopolymers with a variety of well-defined chain lengths were prepared via atom transfer radical polymerization, whereas linear α-polylysine was prepared via ring-opening polymerization of N-carboxyanhydride monomers. Copper-catalyzed azide-alkyne cycloaddition was employed for 'click' conjugation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 45 publications
(63 reference statements)
3
71
1
1
Order By: Relevance
“…These results contrast with arecent study where star-shaped block copolymers of polylysine and mannose-functionalized polymethacrylates exhibited enhanced microbial targeting and activity relative to those lacking the mannose. [26] Theantibacterial activity of the glucoside polymer GluP P was similar to that of ManP P ,w ith MBC values of 46 mm and 4.3 mm against E. coli and S. aureus,r espectively.A pproximately 2-fold lower selectivity indices of 1.5 and 16 for E. coli and S. aureus, respectively were obtained due to this polymers lower HC 50 .B oth sugar-functionalized polyphosphoniums showed lower activity against Gram-negative E. coli than Gram-positive S. aureus,atrend that has been reported previously for polytrialkylphosphonium biocides. [16] The hydrophilic/lipophilic balance between these two biocides is the same,sot argeting capabilities of mannose aside,i tisn ot surprising that they would exhibit the same antibacterial activities.The higher hemolytic activity of GluP P might result from the binding of glucose to glucose transporters on the red blood cell surface.…”
Section: Angewandte Chemiementioning
confidence: 74%
“…These results contrast with arecent study where star-shaped block copolymers of polylysine and mannose-functionalized polymethacrylates exhibited enhanced microbial targeting and activity relative to those lacking the mannose. [26] Theantibacterial activity of the glucoside polymer GluP P was similar to that of ManP P ,w ith MBC values of 46 mm and 4.3 mm against E. coli and S. aureus,r espectively.A pproximately 2-fold lower selectivity indices of 1.5 and 16 for E. coli and S. aureus, respectively were obtained due to this polymers lower HC 50 .B oth sugar-functionalized polyphosphoniums showed lower activity against Gram-negative E. coli than Gram-positive S. aureus,atrend that has been reported previously for polytrialkylphosphonium biocides. [16] The hydrophilic/lipophilic balance between these two biocides is the same,sot argeting capabilities of mannose aside,i tisn ot surprising that they would exhibit the same antibacterial activities.The higher hemolytic activity of GluP P might result from the binding of glucose to glucose transporters on the red blood cell surface.…”
Section: Angewandte Chemiementioning
confidence: 74%
“…This gives an opportunity to combine the versatility of polymer chemistry with improved cell interaction for biological applications . Studies have demonstrated that glycopolymers offer significantly lower toxicity for mammalian cells than standard polymer‐based nanoparticles …”
Section: Resultsmentioning
confidence: 99%
“…[32,33] Studies have demonstrated that glycopolymers offer significantly lower toxicity for mammalian cells than standard polymer-based nanoparticles. [34,35] However, to date, there has been very little work focused on fabricating synthetic glycopolymer-based materials, and the main focus of available studies has been to exploit the properties of the sugar-lectin interactions as a mechanism to isolate or selectively culture a specific cell type from a heterogeneous population [36,37] or to facilitate enzyme immobilization for delivery purpose. [38] Here for the first time, we report the fabrication of aligned glycopolymer-based electrospun membranes, investigating their mechanical behavior in detail, and presenting that they can successfully provide cell guidance over tenocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the conventional cationic polymers exhibited efficacious bactericidal activity, they often tend to induce hemolysis when they are in contact with red blood cells (RBCs). To address this concern, many efforts have been devoted to develop hemocompatible antibacterial materials . One common strategy is to conjugate bactericidal moieties (e.g., cationic polymers and AMPs) to hemocompatible polymer backbones to combine their merits in bactericidal activity and biocompatibility.…”
Section: Multifunctional Antibacterial Materialsmentioning
confidence: 99%
“…The conjugation of glycopolymer and AMPs provided flexibility in the designing polymer conjugates for on‐demand application by selecting different glycomoieties. To achieve broad spectrum of antibacterial activity toward both Gram‐positive and Gram‐negative bacteria, the four‐arm star polymers containing glycopolymer and α‐polylysine moieties were synthesized in a similar approach . The mannose‐based glycopolymer arms significantly improved the bactericidal efficacy due to the increased binding affinity to the bacterial surface.…”
Section: Multifunctional Antibacterial Materialsmentioning
confidence: 99%